COVID-19 revisiting inflammatory pathways of arthritis - Schett, Georg; Manger, Bernhard; Simon, David; Caporali, Roberto (Nature Reviews Rheumatology, 2020)
Coronavirus disease 2019 (COVID-19) is an infectious disease, caused by severe acute respiratory syndrome coronavirus 2, which predominantly affects the lungs and, under certain circumstances, leads to an excessive or uncontrolled immune activation and cytokine response in alveolar structures. The pattern of pro-inflammatory cytokines induced in COVID-19 has similarities to those targeted in the treatment of rheumatoid arthritis. Several clinical studies are underway that test the effects of inhibiting IL-6, IL-1β or TNF or targeting cytokine signalling via Janus kinase inhibition in the treatment of COVID-19. Despite these similarities, COVID-19 and other zoonotic coronavirus-mediated diseases do not induce clinical arthritis, suggesting that a local inflammatory niche develops in alveolar structures and drives the disease process. COVID-19 constitutes a challenge for patients with inflammatory arthritis for several reasons, in particular, the safety of immune interventions during the pandemic. Preliminary data, however, do not suggest that patients with inflammatory arthritis are at increased risk of COVID-19.
CRIS-Team Scopus Importer:2020-06-26